Effect of 5-aminolevulinic acid-based photodynamic therapy via reactive oxygen species in human cholangiocarcinoma cells - Kang DH (Dove Medical Press, 2011)
Cy Hyun Kim1,2, Chung-Wook Chung1, Kyung Ha Choi1, Jin-Ju Yoo1, Do Hyung Kim1,2, Young-IL Jeong1, Dae Hwan Kang1,21National Research and Development Center for Hepatobiliary Cancer, Research Institute for Convergence of Biomedical Science and Technology, Pusan National University Yangsan Hospital, Yangsan, Republic of Korea; 2School of Medicine, Pusan National University, Yangsan, Republic of Korea The first two authors contributed equally to this work.Abstract: Cancer cells have been reported to exhibit an enhanced capacity for protoporphyrin IX (PpIX) synthesis facilitated by the administration of 5-aminolevulinic acid (ALA). We investigated the effect of ALA-based photodynamic therapy (PDT) on human cholangiocarcinoma cells (HuCC-T1). Since protoporphyrin IX (PpIX), a metabolite of ALA, can produce reactive oxygen species (ROS) under irradiation and then induce phototoxicity, ALA-based PDT is a promising candidate for the treatment of cholangiocarcinoma. When various concentrations of ALA (0.05–2 mM) were used to treat HuCC-T1 cells for 6 or 24 hours, the intracellular PpIX level increased according to the ALA concentration and treatment time. Furthermore, an increased amount of PpIX in HuCC-T1 cells induced increased production of ROS by irradiation, resulting in increased phototoxicity.Keywords: ALA-based photodynamic therapy, HuCC-T1, protoporphyrin IX, ROS